Penurunan Fatigue pada Pasien HIV/AIDS dengan Progressive Muscle Relaxation - Setiawati, Desy; Rayasari, Fitrian; Fauziah, Munaya; Jumaiyah, Wati; Komalawati, Dedeh (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to identify the effect of Progressive Muscle Relaxation (PMR) therapy on reducing fatigue scores in HIV/AIDS patients. The research method uses a pre-post quasi-experimental design with a control group design. The study results showed that giving progressive muscle relaxation therapy to the intervention group decreased fatigue by 8.763 points, with a p-value of 0.000. In conclusion, advanced muscle relaxation therapy can be used as an intervention of choice to reduce fatigue conditions in HIV/AIDS patients for seven days, at least once a day, in the afternoon for 10-20 minutes per exercise, taking into account the factors of Hb levels, duration of ARV use, and psychological factors. Keywords: Fatigue, HIV/AIDS, Progressive Muscle Relaxation